Changing risky drinking practices in different types of social worlds: concepts and experiences. (2nd January 2022) - Room, Robin; MacLean, Sarah; Pennay, Amy; Dwyer, Robyn; Turner, Karen; Saleeba, Emma
Abstract: The 'social worlds' concept has been underutilized in alcohol research. This is surprising given that drinking is primarily a social activity, often a secondary part of a sociable occasion in a social world whose members come together around something they have in common, such as an occupation, a hobby, or an identity. Social worlds which include drinking in their practices often entail encouragements or pressures to drink more, though they may also try to impose some limits on drinking or related behavior. Heavy drinking social worlds may be a useful target for public health interventions aimed at supporting less harmful drinking practices, and this paper moves beyond a theoretical discussion of social worlds and their utility to suggest how the concept might be applied in practical terms. We discuss the various influences and actors that potentially impact on heavy drinking social worlds, and suggest a pragmatic typology of social worlds in terms of five features: activity-based, identification-based, settings-based, worldview-based and social position-based. Most social worlds will be characterized by more than one feature, although it is likely that one will predominate in a given social world. Examples are discussed of changes in drinking norms in heavy-drinking social worlds primarily characterised in terms of each of the five features. Implications are considered for public health programming to reduce risky drinking in such social worlds.